Efficient plasma-catalysis coupling for CH4 and CO2 transformation in a fluidized bed reactor: Comparison with a fixed bed reactor. (15th March 2021) - Bouchoul, Nassim; Touati, Houcine; Fourré, Elodie; Clacens, Jean-Marc; Batiot-Dupeyrat, Catherine
Abstract: The transformation of methane and carbon dioxide by coupling plasma and catalysis was investigated using a fluidized bed reactor and the results, in terms of reactant conversion and yields in products, were compared with those obtained in a fixed bed reactor. A series of alumina, including a commercial sample and various meso-macro materials synthesized in the laboratory, was tested in this study. Their surface areas varied from 260 to 312 m 2 g −1 depending on their calcination temperature. A correlation between reactant conversion and surface area of alumina was highlighted for the plasma-fluidized bed, the best conversions being reached with the alumina presenting the highest surface area. CH4 conversion increased from 8.5 to 12.1% for S = 260 and 312 m 2 g −1 respectively and the CO2 conversion from 3.4 to 6.2% for a deposited power of 4 W, in an excess of CO2 . This correlation was not corroborated for the fixed bed reactor. It proves that an efficient coupling of plasma and catalysis can be expected as soon as solid particle are moving in the gas flow, enhancing the plasma-surface interaction.